O município na ordem federativa do Brasil: a (re)invenção da cidade e o direito à cidade - Cavalca, Renata Falson (2016)
While condensing the repercussions arising from changes engendered by globalization and technology, local urban spaces are subject to readjustments of all kinds - social, economic, environmental, political and legal - to enable the reproduction of urban life. Population density and urban agglomerations intensified social demands and questions concerning the role of the municipality in the political, economic, social and environmental, not only in relation to the provision of services, especially those aimed at education, health, housing, transport, leisure, as well as the guarantee of citizenship rights are essential to human dignity. In this light, the present study is to focus the discussion of issues related to the position of municipal federal entity in the political and legal situation of the Brazilian federation, advocating is the need to (re) city of the invention for the realization of the right to the city. To this end, the proposed theme examines new dimensions and visions of urban space: the city. In light of the processes of urbanization and urban issues, the different forms that take on contemporary reality, recognize up ideas on environmental protection, urban environment, social, economic, cultural, political and environmental, community, citizenship, local government, governance, urban planning, environmental policies, quality of life, sustainable development, urban resilience, environmental ethics, education, local democracy, municipal autonomy and political participation of the community. The study of urban theme speaks to the debate on the effects of socio-spatial transformations in conditioning the political and institutional system of cities, and the challenges to the adoption of decentralized management models based on local governance. To this end, they propose strategies that have accompanied the tools necessary to lead to a change of the reality of urban life. Indeed, the realization of the right to the city calls for the assumption by the local community in decisions about their own development. There, as in the city a public dimension of collective life to be organized. It is precisely this need for organization of public life in the city that emerges from an urban power, political and administrative authority in charge of its management: the municipality. In addition, the city is the intervention framework in which public policies must be guided by clearly formulated policy options and guided by the local interests, and its municipal government, the principal. Thus, the local government, backed by its basic instruments, which are decentralized planning and community participation, is a mechanism of political and economic order with great effectiveness to local development. Hence the value of the city as a privileged field for the learning of democracy and the reconstruction of politics, given the proximity to the local level guard of citizens and their daily needs. With the theme, it intends to contribute to the clarification of these processes, their conflicts in different orders, joints and voltages present in the reality of urban life among the various social actors, especially analyzes to significant responses in discussions on the position and relevance of the role of the Municipality in the federal order of Brazil